Global distribution of treatment resistance gene markers for leishmaniasis. Issue 8 (9th July 2022) - Salari, Samira; Bamorovat, Mehdi; Sharifi, Iraj; Almani, Pooya Ghasemi Nejad
Abstract: Background: Pentavalent antimonials (Sb(V)) such as meglumine antimoniate (Glucantime®) and sodium stibogluconate (Pentostam®) are used as first‐line treatments for leishmaniasis, either alone or in combination with second‐line drugs such as amphotericin B (Amp B), miltefosine (MIL), methotrexate (MTX), or cryotherapy. Therapeutic aspects of these drugs are now challenged because of clinical resistance worldwide. Methods: We reviewedthe recent original studies were assessed by searching in electronic databases such as Scopus, Pubmed, Embase, and Web of Science. Results: Studies on molecular biomarkers involved in drug resistance are essential for monitoring the disease. We reviewed genes and mechanisms of resistance to leishmaniasis, and the geographical distribution of these biomarkers in each country has also been thoroughly investigated. Conclusion: Due to the emergence of resistant genes mainly in anthroponotic Leishmania species such as L. donovani and L. tropica, as the causative agents of ACL and AVL, respectively, selection of an appropriate treatment modality is essential. Physicians should be aware of the presence of such resistance for the selection of proper treatment modalities in endemic countries. Abstract : Geographical distribution of resistant biomarkers gene based on studies carried out on clinical‐resistant isolate.